2018
DOI: 10.3390/ijerph15040598
|View full text |Cite
|
Sign up to set email alerts
|

Legionella spp. Risk Assessment in Recreational and Garden Areas of Hotels

Abstract: Several Travel-associated Legionnaires’ disease (TALD) cases occur annually in Europe. Except from the most obvious sites (cooling towers and hot water systems), infections can also be associated with recreational, water feature, and garden areas of hotels. This argument is of great interest to better comprehend the colonization and to calculate the risk to human health of these sites. From July 2000–November 2017, the public health authorities of the Island of Crete (Greece) inspected 119 hotels associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 34 publications
2
27
1
4
Order By: Relevance
“…Studies conducted in Greek hotels have shown that the risk of water contamination with Legionella sp. in pool showers is 16.42%, in garden sprinklers 7.46%, and in the pool water 5.97% (15). However, research conducted in Japan indicated that 64% of samples from households and 3% from public entities, such as baths or hot springs, showed the presence of Legionella sp (12).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Studies conducted in Greek hotels have shown that the risk of water contamination with Legionella sp. in pool showers is 16.42%, in garden sprinklers 7.46%, and in the pool water 5.97% (15). However, research conducted in Japan indicated that 64% of samples from households and 3% from public entities, such as baths or hot springs, showed the presence of Legionella sp (12).…”
Section: Discussionmentioning
confidence: 98%
“…Najnowszy opublikowany artykuł dotyczy oceny zagrożenia Legionellą sp. w przestrzeniach rekreacyjnych takich jak fontanny, prysznice przy basenach i spa, ogrodowych spryskiwaczach w hotelach, nie obejmuje obiektów nauczania i wychowania (20). W mediach można odnaleźć informacje o wystąpieniu zakażenia Legionella sp.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…If Legionella species are detected, methods such as the use of monochloramine, heat, ultraviolet light, copper-silver ionization and chlorination have been used to reduce the risk to patients [ 67 , 149 , 150 , 151 , 152 , 153 ]. Improvement of chlorination of water supplies may reduce the burden of travel-related legionellosis from non- L pneumophila species [ 151 ]. It is important that detection systems are not solely focused on L. pneumophila , as molecular techniques may help identify the source of infection.…”
Section: Prevention and Public Healthmentioning
confidence: 99%